Technology-Based Driving License Services: Police Breakthrough in Increasing Public Trust - Aulia Nur Rahmah (Advances in Police Science Research Journal, 2021)
The importance of driving licenses (SIM) for the community creates irregularities in the management where there are many cases of SIM service irregularities which indicate that SIM irregularities in the police body are severe and systematic. In addition, the general public does not know the cost that should be for the manufacture or extension of a SIM. The cause of this ignorance results in low information received by the public regarding the provisions for making a SIM and / or the public knows but is powerless so that they do not have the courage to ask interested parties. The theory that the author uses in this study is based on the theory of performance by Bernardin and Russell, the concept of service performance, the dimension of service performance, the concept of management (empowerment) performance, the principles of good governance according to Law no. 28 of 1999, as well as the Composition and Authority of the Police as regulated in Law No. 2 of 2002. The approach used by the author in this study is a qualitative approach and the method used is a field study. The sources used are primary and secondary sources. Data collection techniques used in this study were interviews, observation, and document review. The findings obtained by the authors during the study show that there has been a significant increase in new SIM applicants in the last 2 years. The Regident Unit has made a new breakthrough, namely IT-based and broker-free SIM services, thereby increasing public trust. SIM applicants can do SIM services in a short time. The author's suggestion in this paper is that the need for renewal of facilities and infrastructure to support the performance of members in order to carry out their duties optimally, development of information technology systems, the existence of cooperation units in power to conduct outreach to the public about SIM Online.